Multilingual Communication Practices As A Representation Of The Social Identity Of Central Java-West Java Border Communities - Diah Nadiatul Jannah (PT. Padang Tekno Corp, 2026)
Central Java–West Java border communities live in a multicultural environment where Javanese and Sundanese cultures meet, forming distinctive multilingual communication practices. The use of Javanese, Sundanese, and Indonesian in everyday life functions not only as a means of communication, but also as a representation of the community's social identity. This study aims to analyze the multilingual communication practices of Central Java–West Java border communities and to explain the role of language in representing community social identity. The study uses a descriptive qualitative approach with a literature review method supported by social-contextual reflection. Data were obtained from various scientific sources discussing multilingual communication, social identity, intercultural communication, bilingualism, and multilingualism. The analysis was carried out through the stages of data reduction, theme categorization, meaning interpretation, and conclusion drawing. The findings show that border communities flexibly use Javanese, Sundanese, and Indonesian according to the context of interaction, social relations, and communication needs. The practices of code switching and code mixing are important parts of daily communication as forms of social and cultural adaptation. In addition, language use functions as a symbol of cultural identity, a means of identity negotiation, and a mechanism of social integration in a multicultural environment. The findings affirm that multilingual communication is a representation of dynamic social identity and reflects the ability of border communities to maintain social harmony amid cultural diversity.